Kasus Analisa Ekonomi Atas Hukum Tentang Hukum Anti Monopoli dan Persaingan Usaha - Rahmadayani Rahmadayani; Rezmia Febrina; Yetti Yetti (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Business activities that are now widely carried out by business actors are not free from competition. This competition sometimes leads to breaking the law in order to achieve maximum profits. They even carry out unfair competition/unhealthy competition. This unhealthy business competition will harm the public interest. This competition is now widespread in business activities in Indonesia and other countries in general. Although before the issuance of Law no. 5 of 1999, in fact the regulations regarding unfair business competition are based on article 1365 of the Civil Code regarding unlawful acts and article 382 bis of the Criminal Code.